Innovating aircraft design for better heat-control. (Research'eu results magazine)
EU-funded project TOICA is radically changing the way thermal studies are performed in aircraft design. The project's platforms allow collaborative design and will facilitate early considerations of thermal impacts with potential safety and cost benefits.